Ethiopia Financial Sector Development : The Path to an Efficient Stable and Inclusive Financial Sector - World Bank (World Bank, Washington, DC, 2020)
Ethiopia’s financial sector has, over the past decade, been operating under a financial repression framework used by the government for managing its monetary and foreign exchange policy, and financing of large infrastructure projects and state-owned-enterprises (SOEs). Instruments used under this framework include the central bank financing of the government, a state-dominated banking sector, mandatory financing of priority projects and directed credit, administered interest rates, a captive domestic market for government debt, high liquidity and capital requirements, and strict foreign exchange controls. Over time, the framework has led to the build-up of large macro-financial imbalances; these include a system of fiscal dominance, pressures on inflation, the overvaluation of the Birr, a chronic shortage of foreign exchange, the lack of development of the financial system, a credit allocation skewed toward the public sector, and an overall risk of malinvestment. This report was prepared as part of a technical assistance engagement and was based on a request from the National Bank of Ethiopia (NBE) as an input to support their development of a financial sector modernization roadmap to meet the overall government reform plans. The report provides an insight on operations and challenges in Ethiopia’s financial sector and proposes a framework to help open and transform the current system to meet the country’s future market-oriented growth plan. The report is organized along the NBE Roadmap framework which is aligned across three pillars: (i) financial stability and safety net; (ii) long-term finance and financial markets; and (iii) access to finance and financial inclusion. Opening of the financial sector constitutes a cross-cutting theme.